2019
DOI: 10.3390/ijms20030518
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1/2 Inhibitor Olaparib Prevents or Partially Reverts EMT Induced by TGF-β in NMuMG Cells

Abstract: Poly- adenosine diphosphate (ADP)-ribose (PAR) is a polymer synthesized as a posttranslational modification by some poly (ADP-ribose) polymerases (PARPs), namely PARP-1, PARP-2, tankyrase-1, and tankyrase-2 (TNKS-1/2). PARP-1 is nuclear and has also been detected in extracellular vesicles. PARP-2 and TNKS-1/2 are distributed in nuclei and cytoplasm. PARP or PAR alterations have been described in tumors, and in particular by influencing the Epithelial- Mesenchymal Transition (EMT), which influences cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Recent studies have indicated that the STC-1 gene is closely related to glucose and lipid metabolism as well as to mitochondrial function [29,30]. In addition, PARP or PAR alterations have been described in tumors, speci cally those in uencing EMT [31][32][33]. Our RNA-seq and qPCR results strongly suggest that LAIR-1 inhibits EMT through metabolic pathways.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies have indicated that the STC-1 gene is closely related to glucose and lipid metabolism as well as to mitochondrial function [29,30]. In addition, PARP or PAR alterations have been described in tumors, speci cally those in uencing EMT [31][32][33]. Our RNA-seq and qPCR results strongly suggest that LAIR-1 inhibits EMT through metabolic pathways.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies have indicated that the STC-1 gene is closely related to glucose and lipid metabolism as well as to mitochondrial function [29,30]. In addition, PARP or PAR alterations have been described in tumors, specifically those influencing EMT [31][32][33]. Our RNA-seq and qPCR results strongly suggest that LAIR-1 inhibits EMT through metabolic pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Single treatment of them reduced N-Cadherin and Vimentin, but increased claudin-1 and 2 to inhibit EMT. Schacke et al [ 25 ] reported that olaparib prevented the occurrence of EMT. McElwee [ 20 ] reported that overexpression of PADI2 in mice led to occur EMT in tumor cells, which decreased E-Cadherin expression and increased Snail and Vimentin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, single treatment reduced n-cadherin and Vimentin, but increased claudin-1 and -2 to inhibit EMT. Schack et al [ 25 ]reported that Olaparib prevented EMT from occurring. Furthermore, Chen et al [ 26 ]found that PADI2 was closely related to the process of EMT.…”
Section: Introductionmentioning
confidence: 99%